2011
DOI: 10.1007/s10865-011-9360-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity with goal-oriented mental imagery: a randomized controlled trial

Abstract: Self-regulation theory and research suggests that different types of mental imagery can promote goal-directed behaviors. The present study was designed to compare the efficacy of approach imagery (attainment of desired goal states) and process imagery (steps for enacting behavior) in promoting physical activity among inactive individuals. A randomized controlled trial was conducted with 182 inactive adults who received one of four interventions for generating mental images related to physical activity over a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 45 publications
4
53
2
1
Order By: Relevance
“…For instance, older adults frequently used images of achieving the goals they set (e.g., imaging exercising to lose weight and achieving the goal of losing weight) to motivate themselves to exercise. This is in support of previous research that has shown that goal-oriented imagery can increase PA by motivating individuals not only to pursue their goals but also to commit and extend more effort to achieve their goals (Chan & Cameron, 2012;Schultheiss & Brunstein, 1999). Consequently, goal imagery likely represents part of the self-regulatory behavior and is considered to be an important determinant of PA. Planning imagery is another component of self-regulatory behavior that would also be worth investigating.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…For instance, older adults frequently used images of achieving the goals they set (e.g., imaging exercising to lose weight and achieving the goal of losing weight) to motivate themselves to exercise. This is in support of previous research that has shown that goal-oriented imagery can increase PA by motivating individuals not only to pursue their goals but also to commit and extend more effort to achieve their goals (Chan & Cameron, 2012;Schultheiss & Brunstein, 1999). Consequently, goal imagery likely represents part of the self-regulatory behavior and is considered to be an important determinant of PA. Planning imagery is another component of self-regulatory behavior that would also be worth investigating.…”
supporting
confidence: 88%
“…Previous research on exercise imagery has indicated that it can be an effective strategy to increase and/or maintain PA levels (Giacobbi, Hausenblas, Fallon, & Hall, 2003). For example, Chan and Cameron (2012) found that insufficiently active adults who imaged themselves being physically active reported higher levels of PA at the end of the intervention program compared to before. Studies have also tried to explain how imagery leads to higher levels of PA by focusing on the concept of self-efficacy.…”
mentioning
confidence: 99%
“…Approach imagery seemed to be especially effective in changing motivation and engagement in physical activity of middle-aged adults (Chan & Cameron, 2011). In combination with process imagery, the intervention also produced benefits in the domain of action planning.…”
Section: Encouraging Physical Activitymentioning
confidence: 94%
“…and exercise as "a subset of physical activity that is planned, structured, and repetitive" (p. 126). If imagery can increase physical activity in everyday life for inactive or middle-aged adults (Chan & Cameron, 2011;Kim & Giacobbi, 2009), it might also be a promising strategy for increasing mobility in older adults. Maintaining mobility is key to being able to participate in the society and lead a full life.…”
mentioning
confidence: 99%
“…Anderson (1983) showed that imagining engaging in a behavior (e.g., blood donation) enhanced intentions to do so; to the degree that participants found it easy to imagine the behavior, their intention to adopt it increased. Chan and Cameron (2012) found that when sedentary people were asked, rather than not asked, to imagine themselves engaging in procedures and steps that would lead them to exercise, they reported more subsequent action planning. Gregory et al (1982) demonstrated that imagining themselves using a cable television service increased consumers' intention to subscribe (and their real subscription behaviors).…”
Section: Effects Of Pictures In Health Promotion Ads: the Power Of Pimentioning
confidence: 99%